1997
DOI: 10.3109/02770909709075656
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Eosinophils in Hypertonic Saline-Induced Sputum in Patients with Chronic Nonproductive Cough

Abstract: This study was conducted to examine (1) whether an appropriate sputum can be obtained by inducing with inhalation of hypertonic saline in patients with chronic nonproductive cough and (2) whether eosinophils can be detected in the induced sputum. Appropriate samples were obtained by the induction in 25 of 31 patients with bronchial asthma (BA), 12 of 17 patients with cough-variant asthma (CVA), 17 of 20 patients with bronchodilator-resistant cough associated with atopy (atopic cough, AC), and 23 of 25 healthy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
66
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(72 citation statements)
references
References 17 publications
5
66
0
1
Order By: Relevance
“…The majority of studies in adults suggest that eosinophilic airway inflammation is a feature of chronic cough. FUJIMURA et al [20] found high rates of sputum eosinophilia suggesting that their group of adults with chronic cough may have been asthmatic [20]. NIIMI et al [21] found that percentages of eosinophils and ECP in the cough group were similar to that of confirmed asthmatics and significantly higher than controls.…”
Section: Normalmentioning
confidence: 98%
“…The majority of studies in adults suggest that eosinophilic airway inflammation is a feature of chronic cough. FUJIMURA et al [20] found high rates of sputum eosinophilia suggesting that their group of adults with chronic cough may have been asthmatic [20]. NIIMI et al [21] found that percentages of eosinophils and ECP in the cough group were similar to that of confirmed asthmatics and significantly higher than controls.…”
Section: Normalmentioning
confidence: 98%
“…GIBSON and coworkers [4,21] reported increased numbers of both metachromatic cells and eosinophils in expectorated sputum from nonasthmatic patients with steroid-responsive cough. Induced sputum eosinophilia has also been reported recently in atopic patients with bronchodilator-resistant cough [22]. In the study by BOULET et al [5], BAL cell differentials between nonasthmatic patients with chronic cough and controls differed mainly in metachromatic and epithelial cells.…”
Section: Discussionmentioning
confidence: 89%
“…The first data obtained from 12 patients followed up for 10 years with NAEB diagnosis suggest that it is a benign and self-limiting disease [38]. However, 3 of 32 patients (9%) followed up for at least 1 year with the diagnosis of NAEB were observed to have asthma with typical symptoms and airway hypersensitivity, 5 (16%) of them had fixed airway obstruction, and symptoms and/ or airway inflammation persisted in 21 (66% ) of them [20].…”
Section: The Natural Course Of Non-asthmatic Eosinophilic Bronchitismentioning
confidence: 99%
“…Respiratory tract inflammation can be assessed by sputum induction [38,39]. With this method, which is extremely simple, reliable and noninvasive, adequate sputum can be obtained from lower respiratory tract in 80% of adults and children when hypertonic saline is administered with the help of an ultrasonic nebulizer.…”
Section: Diagnosismentioning
confidence: 99%